Necroptosis in Pulmonary Diseases: A New Therapeutic Target - Wang, Lingling; Zhou, Ling; Zhou, Yuhao; Liu, Lu; Jiang, Weiling; Zhang, Huojun; Liu, Huiguo (Frontiers in Pharmacology, 2021)
In the past decades, apoptosis has been the most well-studied regulated cell death (RCD) that has essential functions in tissue homeostasis throughout life. However, a novel form of RCD called necroptosis, which requires receptor-interacting protein kinase-3 (RIPK3) and mixed-lineage kinase domain-like pseudokinase (MLKL), has recently been receiving increasing scientific attention. The phosphorylation of RIPK3 enables the recruitment and phosphorylation of MLKL, which oligomerizes and translocates to the plasma membranes, ultimately leading to plasma membrane rupture and cell death. Although apoptosis elicits no inflammatory responses, necroptosis triggers inflammation or causes an innate immune response to protect the body through the release of damage-associated molecular patterns (DAMPs). Increasing evidence now suggests that necroptosis is implicated in the pathogenesis of several human diseases such as systemic inflammation, respiratory diseases, cardiovascular diseases, neurodegenerative diseases, neurological diseases, and cancer. This review summarizes the emerging insights of necroptosis and its contribution toward the pathogenesis of lung diseases.